Digital Polarization Programmable Metasurface for Continuous Polarization Angle Rotation and Radar Applications - Wang, Yidan; Shi, Hongyu; Chen, Juan; Yi, Jianjia; Dong, Liang; Zhang, Anxue; Liu, Haiwen (Frontiers in Materials, 2022)
Polarization angle manipulation has been a vital technic in radar applications. This paper proposes and demonstrates a digital polarization programmable metasurface for continuous polarization angle rotation and radar applications. By coding '0' and '1' elements with the two orthogonally polarized waves having 180° phase difference, the polarization angle of electromagnetic (EM) waves can be continually and arbitrarily manipulated. The designed metasurface adopts a patch-transmission and line-patch structure and integrates two polarization channels to carry out 1-bit coding. By rotating the azimuth angle of the designed metasurface mechanically, a continuous rotation of the polarization angle of the transmitted wave can be achieved. Moreover, the transmission around 9.4 GHz can reach higher than 95%. The metasurface sample with optimized structure parameters has been fabricated and tested, where the measurement agrees well with the simulation results. In addition, a radar detection experiment was implemented with an anisotropic target, demonstrating the practical use of the proposed metasurface for polarimetric radar.